INFLUENCE VALUATION OF ASYNCHRONOUS MOTOR CONSTRUCTIVE MODIFICATIONS WITHOUT TOOTH AREA CORRECTION ON ITS ENERGY EFFICIENCY - Irina Romanenko; Maksim Danilov (Вестник Северо-Кавказского федерального университета, 2022)
The working characteristics of asynchronous motor with squirrel-cage rotor were calculated based on verifying computation. The rated efficiency and power factor were obtained from these results. For this engine, a series of verification calculations for the changed length of the magnetic circuit and the number of stator winding was performed. For various combinations of these parameters were received rated and maximum efficiency and rated power factor. It was found the optimal combination of simulated changes, which differs from the original design solution.